(untitled) (gjstudies, 2024)
This research investigates the significant challenges and innovative solutions inInformation Systems auditing as banking institutions increasingly migrate theiroperations to cloud computing platforms. Through comprehensive analysis of 173financial institutions across global markets from 2021 to 2024, this study examineshow banks ensure data security, maintain robust access controls, and preserve comprehensive audit trails in cloud environments. The research develops a novel CloudAudit Maturity Framework (CAMF) that quantifies institutional readiness acrosstechnical, procedural, and governance dimensions. Empirical results demonstratethat banks with mature cloud audit frameworks experience 58% fewer security incidents and 47% better regulatory compliance outcomes compared to institutionswith underdeveloped approaches. The study reveals that data encryption gaps account for 32% of cloud security vulnerabilities, while inadequate access managementrepresents the most significant audit challenge. Findings indicate that successfulcloud auditing requires specialized technical expertise, advanced monitoring tools,and collaborative governance models between banks and cloud service providers.This research contributes both theoretical advancements in cloud security auditingand practical implementation guidelines for financial institutions navigating digital transformation while maintaining robust information systems governance andregulatory compliance